Annotated Bibliography Perpustakaan Tun Abdul Razak Issue 1/2019 - Jabatan Perancangan dan Pembangunan Perpustakaan, Bahagian Sumber Bercetak (Perpustakaan Tun Abdul Razak, 2019)
The Annotated Bibliography Perpustakaan Tun Abdul Razak UNIVERSITI TEKNOLOGI MARA SHAH ALAM is a list of library materials added into the collection of Perpustakaan Tun Abdul Razak in Shah Alam Campus and all others campuses in UiTM. It will be published quaterly (4 issues a year). The listed materials are available in various formats obtained through the procurement process including donation.